Pidana Kerja Sosial Dalam Membatasi Kelebihan Penghuni Di Lembaga Pemasyarakatan - Ahmad Fajri (Universitas Islam Indonesia, 2019)
Correctional Institutions (Lapas) that suffer from excess occupants continue to occur throughout the territory of Indonesia. Based on the data from the Directorate General of Corrections, as of January 2019, excess occupants in Indonesian penitentiaries have reached 101%. This is dangerous from various sides, from the health to psychology. Therefore, this study was conducted to analyze the provisions of social work penalties in limiting the excess occupants in penitentiaries based on criminal theory and criteria of criminal conduct that could be subject to social work as criminal sanctions. This research is a normative study that examines written law from the aspects of theory, history, philosophy, and comparison, using a conceptual and juridical approach. Based on an analysis of the formulation of the problem, this study concludes, first, with the suitability of social sanction and criminal theory, social sanction has the prospects to be applied in Indonesia. In fact, if its role is very effective and efficient in achieving the goal of punishment, it does not rule out the possibility of a social sanction to be a single principal and can be applied to serious offenses and as a condition for clemency to be applied. That is because the advantages of social sanctions, both in terms of its humanistic and economic approach. Second, For its criteria, social work sanction functions as an alternative to a short/mild prison sentence, less than six months, and a first category of light fines, which is a maximum of ten million rupiah. In the draft of 2017 Penal Code Bill, this sanction is not used within the framework of clemency/mercy.